TREES AND REGENERATION IN RUBBER AGROFORESTS AND OTHER FOREST-DERIVED VEGETATION IN JAMBI (SUMATRA, INDONESIA) - Hesti L. Tata; Meine van Noordwijk; Marinus Werger (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2008)
The rubber agroforests (RAF) of Indonesia provide a dynamic interface between natural processes of forest regeneration and human’s management targeting the harvesting of latex with minimum investment of time and financial resources. The composition and species richness of higher plants across an intensification gradient from forest to monocultures of tree crops have been investigated in six land use types (viz. secondary forest, RAF, rubber monoculture, oil palm plantation, cassava field and Imperata grassland) in Bungo, Jambi Province, Indonesia. We emphasize comparison of four different strata (understory, seedling, sapling and tree) of vegetation between forest and RAF, with specific interest in plant dependence on ectomycorrhiza fungi. Species richness and species accumulation curves for seedling and sapling stages were similar between forest and RAF, but in the tree stratum (trees > 10 cm dbh) selective thinning by farmers was evident in a reduction of species diversity and an increase in the proportion of trees with edible parts. Very few trees dependent on ectomycorrhiza fungi were encountered in the RAF. However, the relative distribution of early and late successional species as evident from the wood density distribution showed no difference between RAF and forest.